Deficit Financing Components, Inflation and Capital Formation in Nigeria: Evidence from a Direct and Indirect Analysis - Aladejare, Samson Adeniyi (Asian Journal of Economic Modelling, 2022)
Deficit financing occasioned by low domestic savings and low capital formation, have characterised the Nigerian economy since the 1970s with attendant increase in inflation. Empirical studies on Nigeria have shown that deficit financing directly affects inflation and capital formation when examined independently. However, little attention has been paid to a simultaneous investigation of the direct and indirect effects of deficit financing components on inflation and capital formation for Nigeria. Consequently, this study was designed to fill this gap through time series data and the instrumental variable approach. The study found that deficit financing components indirectly impacted on inflation and capital formation in Nigeria from 1970 to 2017; as against the direct effects reported in empirical studies. Also, inflation was found to have had adverse effect on capital formation. Hence, better synergy of fiscal and monetary policies to effectively tame inflation and ensure growth of capital formation was recommended.